Implementation quality of post graduate diploma program in public higher learning institutions in Malaysia - Darusalam, G.; Othman, A.J. (2011)
The Post Graduate Diploma Program (PGDP) is an educational program offered to university graduates who opt to be teacher. The duration of the PGDP teacher training course is one year. This reasearch, which is the form of program assesment through Model Budgeting System (MBS) conceptual framework, is intended to improve the program activity performance from the aspects of effectiveness, suitability, efficiency and economy. This research was carried out by employing survey method with the combination of quantitative and qualitative (mix methods) approaches. This research consisted of four samples chosen randomly from PGDP graduate teachers (n= 471), lecturers teaching PGDP (n=35), PGDP coordinators (n=4) and school administrators (n=43). Eleven public libraries were chosen as the research location. Two instruments were utilized for this research; questionnaires and open questions constructed by the researcher based on MBS conceptual framework, divided into four subsections of effectiveness, suitability, efficiency and economy. The Alpha reliability (Ó) obtained was between 719 and 914. The Nunally (1978) and Stufflebeam (1972) interpretation matrix is employed to evaluate the level of implementation quality for PGDP. The result found that the implementation quality of PGDP in public higher leraning institutions from the aspect of program suitability was at average high level based on a mean value of 3.86. Lastly, from economy aspect, the research found that majority of universities that implemented PGDP stated budgeting did not affect the PGDP activities., outcomes and products. To overcome wastage, most universities that conducted PGDP always come out with a plans such as reducting program activities which require high costs, proliferating internal programs and conducting collaborations between faculties of education in the succeeding PGDP.